Calibrating the Final Results of the Hay System of Job Evaluation Using Urgency, Seriousness, and Growth (USG) Analysis in Indonesia - Haspul Naser Haspul Naser; Nurwulan Kusuma Devi; Nurul Wahdini (Journal of Indonesian Economy and Business, 2022)
Introduction/ Main Objectives: The research argues that the job evaluation process may not reflect a sense of justice, that is, in most cases, the decisions of the board of directors (BOD) appear to be biased. Background Problems: Lack of transparency and unfairness in job evaluations may create disharmony in the workplace. Novelty: The researchers used the Urgency, Seriousness, and Growth (USG) analysis to find the root cause of employees’ dissatisfaction because of unfairness in the final job size, which may impact the wages. The researchers were also required to be familiar and have experience with the Hay System. Research Methods: To adjust the job size and to promote fairness, the Hay System needs to be strengthened with the USG analysis. This study uses a qualitative approach and requires a more in-depth analysis to obtain the best results. Findings/ Results: The job evaluation only refers to the Hay System. The job analysis, benchmark, and survey are not used as a reference or to interview the managers. If the Hay system is solely used, the final result of the job evaluation can be biased;. therefore, it is necessary to get a second opinion to create a sense of fairness. One of the tools to calibrate the final result of job evaluation is the USG analysis. Conclusion: USG analysis is to provide a second opinion and can also strengthen the job size analysis with the job reference level.